My cousin Rachel [videorecording (DVD)] - Michell, Roger, 1956-; Claflin, Sam, 1986-; Weisz, Rachel, 1970-; Glen, Iain, 1961-; Grainger, Holliday, 1988-; Du Maurier, Daphne, 1907-1989 (20th Century Fox Home Entertainment, 2017)
The movie is based on the 1951 novel by Daphne Du Maurier and tells the story of a young Englishman who plots revenge against his mysterious, beautiful cousin, believing that she murdered his guardian.